Salmonella Infantis Adhesion to Various Surfaces and In Vitro Antimicrobial Efficacy of Commercial Disinfectants - Katja Kranjc; Jana Avberšek; Neva Šemrov; Olga Zorman-Rojs; Darja Barlič-Maganja (Pathogens)
Salmonella Infantis poses a significant challenge in poultry production due to its persistence and resistance to disinfectants. This study investigated the survival of the S. Infantis strain on different surfaces and evaluated the efficacy of disinfectants in both preventing and treating biofilms. The survival of the tested S. Infantis strain was assessed on plastic and stainless steel surfaces after 24 and 48 h. The minimum inhibitory concentrations (MICs) of five disinfectants were determined, and their antiadhesion effectiveness was evaluated using crystal violet. The efficacy of biofilm treatment was evaluated by cell culturability. The results showed that the adhesion of S. Infantis was significantly higher on the plastic surface. The disinfectants were effective at reducing biofilm formation only within the first 24 h. Fresh solutions of disinfectants based on quaternary ammonium compounds exhibited the highest antimicrobial efficacy, while chlorocresol was the most effective for both the prevention and treatment of biofilms. The study results suggest that the presence of plastic surfaces may contribute to the dissemination of Salmonella. Additionally, the effectiveness of disinfectants varied based on storage conditions and contact time, while biofilms demonstrated reduced susceptibility compared to planktonic cells. However, given the laboratory scale of this study, further validation on a commercial scale is necessary to confirm these findings.